2016
DOI: 10.1007/s11060-016-2145-6
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β and stem cell markers are highly expressed around necrotic areas in glioblastoma

Abstract: Invasion into surrounding normal brain and resistance to genotoxic therapies are the main devastating aspects of glioblastoma (GBM). These biological features may be associated with the stem cell phenotype, which can be induced through a dedifferentiation process known as epithelial-mesenchymal transition (EMT). We show here that tumor cells around pseudopalisading necrotic areas in human GBM tissues highly express the most important EMT inducer, transforming growth factor (TGF-β), concurrently with the EMT-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…[48][49][50] Alkaline phosphatase (ALPL) is a stem cell marker, that is highly expressed around necrotic areas within the tumour, and high expression of ALPL and CD133 (another stem cell marker) has been associated with poor prognosis for patients. 51 The mAb therapy against ELTD1 was successful in down-regulating ALPL. Glioma stem cells (GSC) are the main cause of GBM recurrence after therapy and are characterized by CD133.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50] Alkaline phosphatase (ALPL) is a stem cell marker, that is highly expressed around necrotic areas within the tumour, and high expression of ALPL and CD133 (another stem cell marker) has been associated with poor prognosis for patients. 51 The mAb therapy against ELTD1 was successful in down-regulating ALPL. Glioma stem cells (GSC) are the main cause of GBM recurrence after therapy and are characterized by CD133.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our RNA-sequencing data demonstrated that 3 of the genes (SCN5A, L1CAM, BMP2) affected with the anti-ELTD1 treatment that were directly associated with gliomas influenced and interacted with Notch signalling. Alkaline phosphatase (ALPL) is a stem cell marker, that is highly expressed around necrotic areas within the tumour, and high expression of ALPL and CD133 (another stem cell marker) has been associated with poor prognosis for patients 51. However, the RNA-sequence analysis did not show specific gene changes with Notch.Aside from the possible relationship with Notch, the RNA-seq data gave further insight as to what pathways the anti-ELTD1 treatment is targeting.…”
mentioning
confidence: 99%
“…TGF-β is well conserved in evolution, and it regulates multiple cell phenotypes such as adhesion, growth, apoptosis, differentiation and fibrosis [33]. In human cells, the TGF-β signaling pathway contains three ligand isoforms TGF-β1/2/3) and two TGF-β transmembrane receptors (TGFBR I/II).…”
Section: Tgf-β Signaling Pathwaymentioning
confidence: 99%
“…Some studies have confirmed that E-cadherin also could be suppressed by TGF-β through ZEB, Snail and HMGA2. Another interesting finding is the discrepant expression of TGF-β existing between the necrotic and non-necrotic areas of many tumors [33].…”
Section: Tgf-β Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation